Correlation of SPAD Value with Intensity of Blast Disease Attack at Various Ages of Rice Paddy - Sudiarta, I Made; Wijaya, I Made Anom S.; Sulastri, Ni Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Rice is an important food crop that serves as the staple food for more than half of the world's population. Rice plant health is crucial in determining crop yields, and chlorophyll content is closely related to plant health, which affects rice production. A decline in plant health makes crops more susceptible to diseases, such as blast disease, which can be observed on the leaves by changes in greenness. SPAD (Soil Plant Analysis Development) is a simple tool used to measure chlorophyll content in plant leaves. This study aimed to (1) determine the relationship between SPAD values and the intensity of blast disease attacks, and (2) obtain a correlation value between SPAD and disease intensity. Data collection was conducted in Medium Village, Badung Regency, from rice aged 71 to 94 days after planting (HST). Measurements were taken diagonally across three rice fields, with five points per plot, nine clumps per point, and SPAD measured in three sections of each leaf (upper, middle, and lower). Disease intensity was determined from the distribution of spots on the leaves. The development of disease intensity and SPAD over time showed that high disease intensity corresponded with low SPAD values, while high SPAD values corresponded with low disease intensity. The results indicated a linear relationship between SPAD and disease intensity, with a correlation value of 0.8634 (86%), indicating a very strong correlation since it exceeds 0.75 (75%).